Nanostructure-property relationship of two perfluorinated sulfonic acid (PFSA) membranes - Choi, Seung-Young; Ikhsan, Muhammad Mara; Jin, Kyeong Sik; Henkensmeier, Dirk (John Wiley & Sons Inc., 2022)
The physicochemical properties of perfluorinated sulfonic acid (PFSA) polymers are closely correlated with their nanostructure. However, their real nano-structural morphology is still controversial because it is difficult to observe their accurate morphology at the nanoscale. Moreover, studies on the nanostructures of the PFSA membranes have been mainly focused on the ionic domain. On this basis, here we describe the crystalline domain of two PFSA membranes as well as their ionic domain based on small-angle X-ray scattering results. Both ionic and crystalline domains showed significant alterations during hydration, and the different behaviors based on the side-chain length of the two PFSA membranes are also described. The short side chain-tethered PFSA membrane (higher ion exchange capacity (IEC)) showed a widespread ionic domain and lacking crystalline domain with their relatively temperature-dependent tendency compared to the flexible long side chain-tethered PFSA membrane (lower IEC). On this basis, the correlation between nanostructure and membrane properties is described from various perspectives.